Website-Based Savings and Loans Data Processing Information System at the Office of Cooperatives and UMKM Medan Helvetia District - Putra, Eka; Krisna, Robi; Wijaya, Rian Farta; Putra, Randi Rian (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
At the Cooperative Office, currently the process of processing savings and loans data  is not optimal because the processing of savings and loans data  still uses manual methods.  Data processing like this can lead to data loss and insecure data storage. Therefore, the research will create a data processing system with sufficient computerization. So that the report that will be needed can be processed appropriately by the medan helvetia sub-district cooperative. From the problems that have been obtained so that a solution arises from its handling by implementing a  web site-based savings and loans information system, so that with the existence of a  web site-based information system,  this research can